2006
DOI: 10.1080/15389580600651103
|View full text |Cite
|
Sign up to set email alerts
|

Cell Phones and Driving: Review of Research

Abstract: Even if total compliance with bans on drivers' hand-held cell phone use can be achieved, crash risk will remain to the extent that drivers continue to use or switch to hands-free phones. Although the enactment of laws limiting drivers' use of all phones is consistent with research findings, it is unclear how such laws could be enforced. At least in the short term, it appears that drivers' phone use will continue to increase, despite the growing evidence of the risk it creates. More effective countermeasures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
144
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(151 citation statements)
references
References 69 publications
3
144
1
3
Order By: Relevance
“…Despite increasing evidence that mobile phone use while driving presents a risk to driver safety, many international (e.g., Törnros & Bolling, 2005) and Australian (e.g., Pennay, 2006) drivers engage in this behaviour (McCartt et al, 2006;Svenson & Patten, 2005;Wiesenthal & Singhal, 2005). A large scale self-report study in Australia found that 43% of mobile phone owners used their mobile phone while driving to answer calls, followed by making calls (24%), reading (16%), and sending (7%) text messages.…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing evidence that mobile phone use while driving presents a risk to driver safety, many international (e.g., Törnros & Bolling, 2005) and Australian (e.g., Pennay, 2006) drivers engage in this behaviour (McCartt et al, 2006;Svenson & Patten, 2005;Wiesenthal & Singhal, 2005). A large scale self-report study in Australia found that 43% of mobile phone owners used their mobile phone while driving to answer calls, followed by making calls (24%), reading (16%), and sending (7%) text messages.…”
Section: Introductionmentioning
confidence: 99%
“…This might be largely due to the fact that mobile phone use while driving requires visual, physical and cognitive attention of the driver (Caird et al, 2008;Horrey et al, 2006;McCartt et al, 2006;Olson et al, 2009;Strayer et al, 2006). Brookhuis et al (1991) contended that mobile phone use (for calling and texting) whilst driving significantly decreases drivers' vehicle control ability resulting in a. four-fold increase in the risk of RTCs (Redelmeier and Tibshirani, 1998).…”
Section: Evidence Of An Association Between Mobile Phone Use While Drmentioning
confidence: 99%
“…15 Mobile phone use while driving has been associated with increased incidence of road traffic accidents. 16,17 However, in recent times, some of the studies have focused on the psychosocial consequences of mobile phone use. A recent prospective study showed that at 1 year of follow-up, increased mobile phone use is associated with symptoms of depression in subjects of either gender and increased sleep disturbances in men.…”
Section: /Jp-journals-10028-1040mentioning
confidence: 99%